Historical international relations - Leira, Halvard; Carvalho, Benjamin de (Los Angeles : SAGE Publications, 2015)
As a quarry for data, testing-ground for theory and site of investigation, history has been one of the unacknowledged partners of International Relations. The last two decades has witnessed both a substantial increase in the scope of historical IR scholarship and in the sophistication of methodological approaches to history, accompanied by a rapidly increasing (and multidisciplinary) interest in the history of international thought, as well as an ever more sophisticated historiography of the discipline itself. This Major Work is structured in a way to engage with the key recent developments in the field of international relations, providing the reader with an overview of approaches to history in IR; the history of international thought/historiography; and the emergence of the state and the state system. Volume One: Doing Historical International Relations Volume Two: The History of International Thought Volume Three: The State in Historical Perspective Volume Four: The State System in Historical Perspective.
Volume 4 The state system in historical perspective.
Includes bibliographical references.
Keywords: International relations -- History; World politics; Political science